Peningkatan Promosi Produk UMKM Es Cendol Sueger Melalui Penciptaan Foto Katalog - Rena Arriva Dwi Nisaul Hotimah; Sonja Andarini (Yayasan Daarul Huda Kruengmane, 2023)
The development of Micro, Small, and Medium Enterprises (UMKM) requires a strategy implemented in marketing their business products to enhance competitiveness and facilitate business growth, including through improving promotional efforts. One effective method for enhancing promotion is by creating marketing content through a product catalog. The goal of a product catalog is to visually and attractively promote products or services and make them easily shareable through social media, websites, or other marketing channels. This helps increase the interest of potential customers and assists them in making better purchasing decisions. UMKM Es Cendol Sueger is one of the UMKM’s located in Kauman Village that produces a beverage called cendol. However, UMKM Es Cendol Sueger faces a challenge in promoting its products, specifically the lack of a product catalog for each item. In this community service project, the KKNT 24 Group from UPN